Penerapan Slow Deep Breathing terhadap Tekanan Darah pada Pasien Hipertensi di Ruang Kenanga RSUD Limpung Kab Batang - Soimun, Soimun; Rahayu Winarti P (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Hypertension is a chronic disease that can increase the risk of serious complications, including heart disease and stroke. One non-pharmacological approach that can be used to manage the accompanying hypertension is the slow deep breathing technique. This technique aims to provide a relaxation effect, reduce blood pressure management, and help regulate blood pressure in hypertensive patients. Objective: This study aims to analyze the effectiveness of the application of slow deep breathing on blood pressure in elderly hypertension patients in the Kenanga Room of Limpung Hospital Method: This study used a descriptive method with a case study approach conducted in September 2025. Data were collected through blood pressure measurements before and after the intervention, and using a blood pressure management questionnaire. The intervention was carried out for three consecutive days, with repeated administration of the slow deep breathing technique. Results: The results showed that there was a significant decrease in blood pressure after the intervention. Before the intervention, the average blood pressure of respondents was high, with the highest value of 202/116 mmHg and the lowest 148/100 mmHg. After the intervention, blood pressure decreased gradually, with an average decrease of 6-15 mmHg. Conclusion: Slow deep breathing has been shown to be effective in lowering blood pressure levels in people with hypertension. This technique can be used as a complementary therapy in the management of hypertension in patients.